Financial Inclusion of Business Players in Mediating the Success of Small and Medium Enterprises in Indonesia - Riwayati, Hedwigis Esti (International Journal of Economics and Financial Issues, 2017)
The aim of this research is to analyse the success of small and medium enterprises that are mediated by financial inclusion of business players and the role of financial inclusion in increasing the success of small and medium enterprises. The unit analysis of this research is the small and medium business players, the stone craftsmen in Magelang Regency, Central Java, Indonesia. The data used in this research are primary data obtained from questionnaires distribution to 76 stone craftsmen. Partial Least Square program is used as data processing tool. Internal and external factors a significant positive effect on the success of small and medium enterprises of stone craftsmen in Magelang Regency, Indonesia. Financial inclusion of business players is able to mediate the determinants of the success of small and medium enterprises. Keywords: financial inclusion, internal and external factors, success of small and medium enterprises. JEL Classifications: G40, L26